Depressive symptoms and suicidal ideation in nurses and physicians care hospital - Khivia Kiss Silva Barbosa; Kay Francis Leal Vieira; Estela Rodrigues Paiva Alves; Nereide Andrade Virgínio (Universidade Federal de Santa Maria, 2012)
Objective: To investigate the presence of depressive symptoms and suicidal ideation among nurses and doctors in hospital care. Methods: This is a descriptive research with quantitative approach, which included 100 subjects - 50 nurses and 50 physicians working in hospitals in the city of João Pessoa, Brazil. We used the Beck Depression Inventory, Scale for Suicide Ideation, Beck and a sociodemographic questionnaire with quantitative analysis. Results: Based on the analysis of data showed that 30% of the sample had depressive symptoms - 20% and 10% nursing care. The presence of suicidal ideation was found in 4% sample. It was found also that all of them also had depression, which shows a strong relationship between the two phenomena. Conclusion: The prevalence of depressive symptoms and suicidal ideation among health professionals were elevated. They act contrary to what is expected of this population in view of their professional activities